PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII A4 MTs DARUL HIKMAH PEKANBARU DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) - Anisa Shaliha; Syofni Syofni; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was classroom action research with two cycles. The purpose of this research was to improve the learning process and the students’ mathematics learning result at class VII A4 at MTs Darul Hikmah Pekanbaru through the implentation cooperative learning type Two Stay Two Stray (TSTS) especially on social arithmetic topic. The research instruments were learning devices which were syllabus, lesson plan (RPP), and student woksheet (LKS) and the instruments of collecting data were observation sheets and students’ mathematics test. The subject of this research was the students at class VII A4 at MTs Darul Hikmah Pekanbaru which consisting of 24 girls with heterogeneous ability. Based on the analyzed of students and teacher activity after implemented the cooperative learning type TSTS, it can be concluded that there was an improvement of learning process at each cycles. Students’ participation was more active and become more independent through the learning process. The analyzed of students’ mathematics learning result data shows that there was an improvement of students’ mathematic learning result in second cycle. There were 16,67% students that reach KKM in UH I, and its improved in UH II which 54,17% students who reach KKM. Based on the result above, it could be concluded that the implementation of cooperative learning type TSTS can improve the learning process and the students’ mathematics learning result at class VII A4 at MTs Darul Hikmah Pekanbaru.Key Word: mathematics learning result, cooperative learning, two stay two stray, classroom action research